Contention-Based Geographic Forwarding Strategies for Wireless Sensors Networks - Lima, Carlos H. M. de [UNESP]; Nardelli, Pedro H. J.; Alves, Hirley; Latva-aho, Matti (Ieee-inst Electrical Electronics Engineers Inc, 2016)
This paper investigates solutions that combine relay selection algorithms and opportunistic geographic routing strategies for autonomous wireless sensor networks, wherein transmissions often occur over multiple hops. In order to design and assess such contention-based geographic forwarding strategies, we establish an analytical framework that incorporates concepts from probability generating functions (through power series expansion), spatial point processes, and auction theory, as well as Monte Carlo simulations to corroborate analytical results. The investigated strategies are built upon three constituent parts: 1) relay selection algorithm; 2) contention resolution mechanism; and 3) geographic forwarding strategy. We then propose an auction-based algorithm for selecting the relay node that relies on the network topology as side-information. Our results show that geographic solutions that iteratively exploit the local knowledge of the topology to ponder the algorithm operation outperforms established random approaches. Although, there is an intrinsic tradeoff between the time needed to identify a suitable next hop relay and the respective progress that is achieved toward the final destination.
Keywords: Random processes; relay networks; routing protocols; ad hoc networks; transforms; auction theory